2021
DOI: 10.3168/jds.2020-19507
|View full text |Cite
|
Sign up to set email alerts
|

A focus group study of Ontario dairy producer perspectives on neonatal care of male and female calves

Abstract: Providing optimal calf care remains a challenge on many dairy farms and has important implications for the future health, welfare, and productivity of male and female calves. Recent research suggests that male dairy calves receive a lower quality of care early in life than female calves, but further investigation is required to determine the factors that influence this disparity. The objectives of this study were to understand dairy producer perspectives on neonatal calf care practices and explore differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Calf care requires substantial time on dairy farms; however, it results in little to no immediate financial payoff, which is especially true for surplus dairy calves. For example, Wilson et al (18) found for Canadian producers the necessary time and effort to care for newborn calves were barriers to the adoption of better management practices, especially for male calves. In interviews, dairy producers discussed an ethical desire to take good care of neonatal calves, but their actions were frequently misaligned (18).…”
Section: Management On Dairy Farmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Calf care requires substantial time on dairy farms; however, it results in little to no immediate financial payoff, which is especially true for surplus dairy calves. For example, Wilson et al (18) found for Canadian producers the necessary time and effort to care for newborn calves were barriers to the adoption of better management practices, especially for male calves. In interviews, dairy producers discussed an ethical desire to take good care of neonatal calves, but their actions were frequently misaligned (18).…”
Section: Management On Dairy Farmsmentioning
confidence: 99%
“…For example, Wilson et al (18) found for Canadian producers the necessary time and effort to care for newborn calves were barriers to the adoption of better management practices, especially for male calves. In interviews, dairy producers discussed an ethical desire to take good care of neonatal calves, but their actions were frequently misaligned (18). Specifically, male calves often receive worse care after birth than female calves on dairy farms.…”
Section: Management On Dairy Farmsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result the neonatal care of these surplus male calves is often inferior to that which heifer calves receive. Heifer calves are seen as the future of the dairy herd, and therefore, are often given priority to ensure their future productivity (9). Thus, dairy bred bull calves are at a greater risk of not receiving a sufficient quantity of quality colostrum within 24 h of birth, resulting in increased risk of failure of passive transfer (FPT) of antibodies (10).…”
Section: Introductionmentioning
confidence: 99%